The Interesting and Complete Artificial Intelligence (ICAI) – Version 1 - Gajawada, Satish; Mustafa, Hassan M. H. (Transactions on Engineering and Computing Sciences, 2021)
A new field titled “The Interesting and Complete Artificial Intelligence (ICAI)” is invented in this work. In this article, we define this new ICAI field. Four new ICAI algorithms are designed in this work. This paper titled “The Interesting and Complete Artificial Intelligence (ICAI) – Version 1” is just the starting point of this new field. We request Research Scientists across the globe to work in this new direction of Artificial Intelligence and publish their work with titles such as “The Interesting and Complete Artificial Intelligence (ICAI) – Version 1.1”, “The Interesting and Complete Artificial Intelligence (ICAI) – Version 2” or “The Interesting and Complete Artificial Intelligence (ICAI) – Final Version”.